Storytelling through video game artworks "“ Twee kante van 'n storie - Randall, Tasmin Tania (Rhodes University, Faculty of Humanities, Department of Fine Art)
This mini-thesis serves as a supporting document for my Master of Fine Art (MFA) exhibition, 'Twee Kante van 'n Storie'. The exhibition explores my culture and experiences as a 'Coloured' woman in Makhanda through storytelling. I use the term 'Coloured' with quotation marks to remain respectful to those who do not wish to reclaim the term. My minithesis analyses how video games as artworks can be a mode of storytelling and can encourage sociocultural awareness. In my research, I use storytelling as a tool and autoethnography as a methodology to both discuss and influence my practice. For my MFA installation, I have created a digital interactive website that uses the same language as a video game. Throughout my process, I have used two video games, That Dragon Cancer and Boet Fighter, as case studies, in order to help the building and creation of my autoethnographic art video game. My art video game explores my experiences of my culture and living in a small town. Through the creation of four fictionalised characters, which are loosely based on true life experiences and first-hand observations, I can reveal and unpack cultural experiences and biases that I have observed over the years. Each character in the game grapples with one of three prominent themes; stereotypes, 'swagger' and texturism. Furthermore, through using autoethnography as a methodology and the researcher as the phenomenon (Ellis, 2004: 45). This study contributes to the gap in 'Coloured' cultural diversities that exist outside the lens of the Western Cape experience. This is a perspective not commonly found within academia.
Keywords: Colored people (South Africa) -- Ethnic identity; Colored people (South Africa) in art; Storytelling in art; Digital art; Browser game; Art Video games; Autoethnography; Stereotypes (Social psychology) in art; Discrimination based on hair texture; Swag